Keefektifan Konseling Kelompok dengan Teknik Permainan untuk Meningkatkan Kepercayaan Diri Remaja - Toy, Rodian O; Malelak, Erly Oviane (JKI (Jurnal Konseling Indonesia), 2023)
There are several phenomena related to adolescent self-confidence, namely feeling ashamed of appearance, not being able to socialize, not being able to voice their opinions when in public and they are given the opportunity to ask questions, they are more silent, and unable to display their skills because they are ashamed of their classmates. This study aims to see how effective group counselling with game techniques is to increase adolescent self-confidence. The research method used is the experimental method of one group pre-test and post-test design. The research subjects consisted of 5 students with low self-confidence who participated in group guidance activities with playing techniques for 6 sesions. The results showed that group caunselling services with game techniques were effective in increasing adolescent self-confidence.